Transitioning from online teaching to blended teaching in the post-pandemic era: What has COVID-19 taught us? - Sia, Joseph; Chin, Wei Lee; Voon, Mung Ling; Adamu, Adamu Abbas; Tan, Sylvester Chun Kiat (Taylor & Francis, 2023)
Although educators in higher education institutions have embraced online teaching, little research has been conducted on their experience transitioning from online to blended classes. This study aimed to conduct a comparative analysis and present feedback from educators in higher education institutions (HEIs) in Brunei and Malaysia who migrated from online to blended teaching. Fifteen edu-cators at HEIs in Brunei and Malaysia undertook in-depth semi-structured interviews that produced four themes: 1) openness to change from traditional teaching methods, 2) institutional assistance for academic resilience, 3) network broadening, and 4) the emergence of the digital divide. The findings assist higher education ministries and HEIs in strategically implementing blended learning in the endemic phase. The proposed recommendations provide insights for authorities to revisit existing education policy frameworks by designing new strategies for adopting technology and adjusting pedagogical approaches in their educational practices. Ultimately, this study contributes to the literature on educators’ readiness and resilience in transitioning from online to blended teaching during the post- pandemic period, particularly in Asian countries.